"التدقيق المحاسبي كآلية لتفعيل الرقابة الجبائية دراسة حالة بمركز الضرائب لولاية الوادي " - عائشة جعفور; وهيبة مسعودي; مريم محدة; احمد حميدي (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة إلى تجسيد الدور الذي يلعبه التدقيق المحاسبي لتفعيل الرقابة الجبائية, إذ يعد التدقيق المحاسبي أحد أهم وسائل الرقابة الجبائية من طرف أعوان مدققين لهم كفاءة مهنية عالية في المجال الضريبي والمحاسبي, حيث أن المشرع منح لهم عدة صلاحيات, في مقابل وضع عدة التزامات التي تعتبر ضمانات ممنوحة للمكلفين بالضريبة بهدف تحسين عملية الرقابة على الملفات الجبائية من كل التجاوزات المستعملة من طرف المكلفين بالضريبة, و الحفاظ على مداخيل خزينة الدولة. ولأجل ابراز مساهمة التدقيق المحاسبي في تفعيل الرقابة الجبائية كونها أداة وقائية ردعية في آن واحد, باعتماد على المنهج الوصفي, التحليلي, الاستنتاجي. من خلال الدراسة التي قمنا بها على ملف جبائي لمكلف خاضع للرقابة الجبائية على مستوى مركز الضرائب لولاية الوادي. توصلت الدراسة إلى أن التدقيق المحاسبي له دور كبير في تسهيل عملية الرقابة الجبائية وجعلها ذات فعالية أكثر فهو يمدها بمعلومات محاسبية صادقة ومطابقة للقوانين الشكلية والموضوعية فتربح بذلك الإدارة الجبائية الوقت والجهد للتحقق منه. " "This study aims to embody the role that auditing plays in enhancing tax oversight. Accounting auditing is considered one of the most important means of tax control by auditors with high professional competence in the tax and accounting field. The legislator has granted them several powers, in return for setting various obligations that are considered. Guarantees granted to taxpayers with the goal of improving the control process over tax files from all the violations used by taxpayers and preserving the state treasury's revenues. To highlight the contribution of accounting auditing in activating tax oversight as both a preventive and deterrent tool, relying on the descriptive, analytical, and inferential approach, through the study we conducted on a tax file of a taxpayer subjected to tax control at the tax center of El Oued province. The study concluded that accounting auditing plays a significant role in facilitating the tax oversight process and making it mor effective as it provides it with honest accounting information that complies with formal and substantive laws, thereby saving time and the effort for the tax administration to verify it. "
مذكرة ماستر